A newly established pediatric high dependency unit in Norway - Interaction with existing pediatric intensive care - Jenny Marie Hilden; Thomas Rajka; Jenny Dalseg; Anne Lee Solevåg (Elsevier, 2021)
Background: In October 2018, our university hospital opened a 2-bed pediatric high dependency unit. We report interactions between this new unit and existing pediatric intensive care. Methods: We included patients who met the requirements for extended monitoring and treatment in a retrospective review of ward admissions 29.10.18-28.10.19. Results: 271 children with 354 ward admissions ('episodes') with extended monitoring and treatment were admitted to the pediatric high dependency unit (77%), the general pediatric ward, neonatal and adult intensive care, post-operative, and adult high dependency units. Frequent diagnoses were bronchiolitis, epilepsy, pneumonia, diabetic ketoacidosis and therapeutic drug overdose. In 37% of the episodes, non-invasive ventilation was provided. Median (interquartile range) age was 2.2 (0.3-14.2) years and 40% was <1 year. Median length of stay was 29 (15-74) hours and the average bed occupancy in the pediatric high dependency unit 1.6. Conclusion: Our results indicate that equipment and staff training should focus on children <1 year of age in need for non-invasive ventilation. There is a potential for more children needing extended monitoring and treatment to be cared for at the pediatric high dependency unit instead of the neonatal and adult intensive care units.